Primarne motoričke stereotipije - Zrnić, Lana (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Motor stereotypies are almost always associated with developmental disorders, such as autism spectrum disorder, intellectual disability, etc. Although they most often occur together with sensory deprivation, they are also recognized as isolated. They occur in children with normal, typical development. These isolated stereotypies are called primary motor stereotypies. Aim. The aim of this paper is to provide a better insight into the specificity of this disorder and to show how it affects people (children), as well as to provide insight into the cause of primary motor stereotypies and possible approaches to treatment. Method. Descriptive method with a review of the literature published in the previous ten years, with a critical review. Inclusion and exclusion criteria were defined. Research on the cause of primary motor stereotypies, primary motor stereotypies themselves, and the treatment of primary motor stereotypies was reviewed. Results. Primary motor stereotypies in children with typical development negatively affect daily activities and disrupt social development, which leads to social stigmatization. Many interventions have been found in children with autism spectrum disorder (stereotypies are one of the main features of autism), but there is very little published research on interventions and treatments for primary motor stereotypies. The root of the problem of primary motor stereotypies is complex and involves certain parts of the cortex and pathways of information transmission. The problem is also the identification of this problem, which further affects the interventions themselves. Conclusion. The cause of primary motor stereotypies is still unknown, and behavioral therapies are the possible treatments for primary motor stereotypies. Based on the available research, there is not much literature on this topic, which provides us with exceptional potential and space for discovering new information and knowledge. With new information, there are many ways to work with these people.
Keywords: primary motor stereotypies; children and adolescents